A monthly effect in stock returns - Ariel, Robert A. (Journal of Financial Economics, 1987)
The mean return for stocks is positive only for days immediately before and during the first half of calendar months, and indistinguishable from zero for days during the last half of the month. This ‘monthly effect’ is independent of other known calendar anomalies such as the January effect documented by others and appears to be caused by a shift in the mean of the distribution of returns from days in the first half of the month relative to days in the last half.